Significance of Ethics for Political Economy Today - Dramalieva, Valentina (Research Papers, 2018)
The article shows how political economy and economics are related as interpretative models of economy and as academic disciplines, and why political economy today includes ethics by necessity in its analyses. Arguments are searched in: the deficiency of economics as the only science analysing the economy; the traditional integration of societal science; the weaknesses in theory and practice stemming from the excessive specialization of social sciences; some examples showing the search for theoretical alternatives in interdisciplinary social research beyond the "pure" economy.